Volatile flavor compounds, total polyphenolic contents and antioxidant activities of a China gingko wine. (1st September 2015) - Wang, Xu; Xie, Kelin; Zhuang, Haining; Ye, Ran; Fang, Zhongxiang; Feng, Tao
Graphical abstract: The aroma compounds in gingko wine are analysis by HS-SPME-GC–MS coupled with OAV and ROC. The in vitro antioxidant activity of gingko wine is measured by DPPH and ABTS method, and compared with five typical Chinese liquors. Highlights: Esters and carbonyl compounds contributed most to the gingko wine aroma. The total phenols content of the gingko wine was 456 mg/L gallic acid equivalents. The gingko wine showed radical scavenging activities based on DPPH and ABTS assay. Gingko wine's antioxidant capacity was higher than typical Chinese liquors. Abstract: The volatile compounds in gingko wine, a novel functional wine, were extracted by head-space solid phase micro-extraction (SPME) and analyzed by gas chromatography–mass spectrometry (GC–MS) coupled with odor activity value (OAV) and relative odor contribution (ROC) analyses. In addition, the total polyphenolic content of gingko wine was determined using the Folin–Ciocalteu reagent, and its antioxidant capacity was evaluated by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and 2, 2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays. Fifty-eight compounds were tentatively identified, including 13 esters, 10 alcohols, 11 acids, 12 carbonyl compounds, 2 lactones, 2 phenols, and 8 hydrocarbons. Ethyl hexanoate, ethyl pentanoate, nonanal, ethyl butyrate and ethyl heptanoate were the major contributors to the gingko wine aroma based on the results of OAV and ROC. The total phenols content of the gingko wine was 456 mg/L gallic acid equivalents, and its antioxidant capacity was higher than those of typical Chinese liquors analyzed in this paper.